Analysis of Hygiene and Sanitation in Junior High School Canteens in Banda Aceh - Masyudi, Masyudi; Ilhamuddin, Ilhamuddin; Indiraswari, Tika; Husna, Husna; Yulidar, Yulidar; Noviyanti, Anita; Yani, Evi Dewi; Rafsanjani, T M (International Conference on Multidisciplinary Research, 2020)
This study aims to see the effect of coaching, supervision and actions given by Banda Aceh junior high school canteen managers on the hygiene and sanitation of the school canteen. A canteen with a low hygiene standard in its physical condition, its raw material for food, food processing and food presentation, can give negative impacts on a child’s health, growth, cognitive development, and nutritional status, which will eventually affect their academic achievement. This research, conducted from 2 to 5th of August 2017, is an analytical survey research with a cross-sectional design. Based on the results of statistical tests using chi-square technique, a positive and significant correlation was found between the canteen manager’s coaching and the canteen’s hygiene and sanitation (p-value = 0.001 0.05), particularly between the supervision, hygiene and sanitation variables (p-value = 0.001 0.05). There is also a strong and significant relationship between the level of canteen maintenance and the canteen’s hygiene and sanitation (p-value = 0.002 0.05). The canteen staff are reported to have complied with the applicable regulations and applied the knowledge they have about the standard hygiene and sanitation. They reported that they regularly maintain personal hygiene when processing the food by washing their hands and keep their work equipment clean. Besides, they maintain the cleanliness of the canteens by throwing waste into the dumping area when the bin is full, and by keeping food and kitchen wares clean. Keywords: Hygiene, Sanitation, Canteen